2006
DOI: 10.1136/thx.2005.047373
|View full text |Cite
|
Sign up to set email alerts
|

Serum carotenoids, vitamins A and E, and 8 year lung function decline in a general population

Abstract: Background: Oxidative stress is thought to have a major role in the pathogenesis of airway obstruction. A study was undertaken to determine whether subjects with low levels of antioxidants (serum b-carotene, acarotene, vitamins A and E) would be at a higher risk of accelerated decline in forced expiratory volume in 1 second (FEV 1 ) as their lungs would be less protected against oxidative stress. Methods: 1194 French subjects aged 20-44 years were examined in 1992 as part of the European Community Respiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…The present findings on the effect of baseline smoking status on FEV1 decline are consistent with those of other studies [18][19][20][21][22]. In addition, within strata for educational level, the FEV1 decline was always fastest in those smoking at baseline.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The present findings on the effect of baseline smoking status on FEV1 decline are consistent with those of other studies [18][19][20][21][22]. In addition, within strata for educational level, the FEV1 decline was always fastest in those smoking at baseline.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, FEV1 decline tended to be slower in never-smoking males of low (versus high) educational level. In addition, in a few studies which used socioeconomic status as a covariate, crude effects on lung function decline were inconsistent [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…For example, subjects who get access to and regularly take prescribed medications may be more likely to adopt generally healthier lifestyles (such as healthy diet and exercise). High dietary intake of antioxidants has been associated with lung function, 47 but we have no information on this for our sample. On the other hand, one might expect subjects with more severe disease to be prescribed more medication.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic surveys among the general population have found that higher dietary antioxidant vitamin consumption (including β-carotene and vitamin E) and/or higher circulating levels of these antioxidants are associated with better pulmonary function and lower rates of lung function decline [29][30][31]. Similarly, in CF, correlations between antioxidant concentrations and lung function have been reported [11,26].…”
Section: Parametermentioning
confidence: 93%